Fairy Sprinkle's magic wand - Joyce, Melanie; Anderson, Nicola ([Sywell] : Igloo Books, 2021)
Fairy Sprinkle has just got her first wand and she can't wait to start casting spells. Join Sprinkle and her fairy friends on a magical adventure in this sparkling tale, perfect for an enchanting storytime.
"A magical story full of sparkle."--Cover.
Keywords: Fairies -- Juvenile fiction